P78 Is a nurse-led community screening programme for hepatitis C making an impact in the Cheshire area?. (20th September 2022) - Lyons, Phoebe; Rose, Jayne; Higham, Lucy; Maheswaran, Tina; Prasad, Yash
Abstract : Introduction: Hepatitis C (HCV) is a blood borne virus that is curative in over 90% of cases. The NHS England HCV Elimination Programme is working to eliminate HCV in advance of the WHO goal of 2030, with initiatives in areas such as primary care, sexual health services and community outreach. High risk groups for HCV include people who inject drugs (PWID), and those who have experienced homelessness. These people tend to be difficult to reach, under-served and at high risk of falling out of the care pathway. During the COVID-19 pandemic, homeless people in a selected small city were housed in empty hostels and hotels. This provided an opportunity for liver specialist nurses (LSNs) to visit these locations, test a high risk population for HCV and commence treatment where necessary. Method: A week-long screening programme has been carried out four times since 2020, led by LSNs and aided by HCV charity workers. Places where high risk groups are known to visit were targeted, including homeless services, hostels and city-centre streets. Rapid HCV antibody tests were used and if positive, further rapid PCR testing was done to detect RNA and distinguish between current and past infection. If RNA was detected, patients were provided with direct-acting antiviral medication. Results: Data from the three most recent weeks of screening were analysed. 354 people were tested. 47 (13.3%) were confirmed HCV RNA positive, 44 (93.6%) of which were commenced on treatment. Reasons that prevented treatment included being unable to contact the patient, death, or contraindications. 22 (6.2%) were identified as having achieved sustained virological response (SVR) from historical antiviral courses. 5 (11.4%) that have been treated during the programme have been confirmed SVR so far. Out of the positives identified, 19 (40.4%) were PWID (current or previous drug injecting), 5 (10.6%) had no history of injecting drugs, and in 23 (48.9%) it was unknown. Conclusion: Increased access to treatment is the lead reason for a reduction in chronic HCV infection among people who inject or have previously injected drugs. This screening programme is benefiting a small city community for those at the highest risk of HCV, and having a positive impact towards the elimination goal. The LSNs are able to visit people who otherwise may be lost from the care pathway. By being able to revisit the same locations each time, HCV positive people are being treated and receiving appropriate follow-up care.